CYCLES OF CONVERGENCE AND DYNAMICS OF GROWTH IN THE SMARTPHONE INDUSTRY - Calvosa, Paolo (European Scientific Journal, ESJ, 2015)
Over the last few years, with the definitive manifestation of the effects of the ‘digital revolution’, a convergence process has taken place and through which the boundaries of the Information and Communication Technologies industries have become increasingly ‘blurred’ and unstable. Amongst the ICT industries in which the convergence process has brought about the most relevant changes, there appears that of the mobile phones. This industry has been characterized by a series of cycles of convergence which have favoured the emergence of hybrid mobile devices, the smartphones. Worldwide sales of smartphones to end users totalled 1.2 billion units in 2014, a 29 per cent increase from 2013. Sales of smartphones in 2013 exceeded annual sales of feature phones for the first time. The work analyzes the effects of the process of digital convergence on the dynamics of growth of the smartphone industry. In particular, the paper: identifies the various cycles of convergence which have contributed towards the growth of the smartphone industry; analyzes, in relation to the various cycles of convergence, the main drivers of convergence, the overlapping industries and the types of convergence taken place; analyzes the impact of the various cycles of convergence on the development phases of the main industries affected by the convergence process.